1993
DOI: 10.1007/bf00788879
|View full text |Cite
|
Sign up to set email alerts
|

Effect of changes in aortic pressure and in coronary arterial pressure on left ventricular geometry and function Anrep vs. gardenhose effect

Abstract: Sudden increases in aortic pressure (AoP, mm Hg) are associated with increases in left ventricular (LV) function which persist even after diastolic volume has returned to its initial value (Anrep effect). Likewise, increases in coronary arterial pressure (CAP, mm Hg) are associated with improved LV function (gardenhouse effect). In situ, increases in AoP are paralleled by increases in both CAP and coronary blood flow, i.e., oxygen supply. We investigated the individual contributions of AoP and CAP increases on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…According to present knowledge, other factors that may alter the dP/dt values after increasing AP are shortening deactivation (21)(22)(23)(24), the Anrep effect (15,18,19) and variations in coronary flow (25) or coronary perfusion pressure (26). Previous studies from our laboratory have shown that large increases of developed force (27) and coronary perfusion (28) do affect left ventricular performance in the intact canine left ventricle.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…According to present knowledge, other factors that may alter the dP/dt values after increasing AP are shortening deactivation (21)(22)(23)(24), the Anrep effect (15,18,19) and variations in coronary flow (25) or coronary perfusion pressure (26). Previous studies from our laboratory have shown that large increases of developed force (27) and coronary perfusion (28) do affect left ventricular performance in the intact canine left ventricle.…”
Section: Discussionmentioning
confidence: 86%
“…At present, two known factors are suggested as potentially affecting the rate of myocardial force generation when afterload changes: the Anrep effect (15,(18)(19)(20) and the shortening deactivation (21)(22)(23). Until (20) convincingly demonstrated the occurrence of the Anrep effect in muscle strips specially instrumented in order to obtain "physiological" contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of the aortic pressure could affect the values of dP/dt, inducing variations in the afterload 8,23 , in the perfusion pressure and in the coronary flow [24][25][26][27] . A series of publications 3,7,8,23 report that the maximal values of dP/dt are directly proportional to the levels of BP; others 9,28,29 , however, suggest that the aortic pressure has no influence on the dP/dt.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced afterload immediately increases the beat volume, thus reducing residual volume and end-diastolic pressure. Homeometric autoregulation (Anrep effect) counteracts, re-adjusting the end-diastolic pressure within a series of beats [19,21,31]. Such adjustment settles during the mounted guinea pig hearts adapt to the artificial circulation.…”
Section: Heterometric Autoregulative Component (Frank-starling)mentioning
confidence: 99%